1980
DOI: 10.1017/s0003356100023849
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of feed additives in enhancing performance of growing pigs

Abstract: BSTRACTThe efficacy of feed additives in enhancing the performance of growing pigs, together with the effect of different protein levels (18 v. 16% from 13 to 18 kg body weight and 16 v. 14% from 18 to 39 kg body-weight), were evaluated in three experiments with 412 pigs. In Experiment 1, from 13 to 39 kg body weight, pigs receiving 55 p.p.m. carbadox (C) produced a greater (P<0-05) average daily live-weight gain than did the non-medicated (NM) pigs and those receiving 275 p.p.m. chlortetracycline-sulphamethaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…These results further confirm other recent reports (Zivkovic and Zlatic, 1979;Moser et al, 1980;Veum et al, 1980) concerning the efficacy of carbadox (a synthetic antibacterial compound not used in human medication) in enhancing the performance of young, growing pigs. A survey of European Association of Animal Production member countries (Braude, 1978) revealed that carbadox was approved for use in swine feeding in 13 of the 19 European countries surveyed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results further confirm other recent reports (Zivkovic and Zlatic, 1979;Moser et al, 1980;Veum et al, 1980) concerning the efficacy of carbadox (a synthetic antibacterial compound not used in human medication) in enhancing the performance of young, growing pigs. A survey of European Association of Animal Production member countries (Braude, 1978) revealed that carbadox was approved for use in swine feeding in 13 of the 19 European countries surveyed.…”
Section: Discussionsupporting
confidence: 92%
“…Carbadox, a synthetic antibacterial compound, has been shown to promote growth in young pigs (Thrasher et al, 1969;Yen et al, 1976;Moser et al, 1980;Veum et al, 1980). The mode of action whereby carbadox stimulates weight gain of pigs has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…In different countries carbadox is also used as a feed-additive to promote animal growth (4, 8,10). The legally permitted dosage in the European Community is 50ppm.…”
Section: Introductionmentioning
confidence: 99%
“…In pig husbandry growth promoting agents are ubiquitous (2, 18,21,23). Of the grow-promoting agents used in the Netherlands carbadox is one of the most popular.…”
Section: Introductionmentioning
confidence: 99%